2018
DOI: 10.1016/j.biocon.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating scenarios of landscape change for Sunda clouded leopard connectivity in a human dominated landscape

Abstract: The forests of Borneo support some of the highest biodiversity in the world, yet have experienced among the world's highest rates of deforestation. Such rapid forest loss and associated fragmentation reduces the availability of suitable habitat for wildlife and creates dispersion barriers. Understanding the prevalence and impacts of this anthropogenic disturbance, and developing ways in which to mitigate such changes, is thus critical to the conservation of Borneo's wildlife. Here, we applied a path selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…Closed‐canopy forests are a primary requirement for this semi‐arboreal species (Cushman et al., ; Sollmann, Linkie, Haidir, & Macdonald, ; Tan et al., ). Conversely, deforestation and subsequent land conversion to large‐scale palm and Acacia plantations have been identified as major threats for both the mainland (Tacconi, ) and Sunda (Cushman et al., ; Hearn et al., ; Hearn, Cushman, Goossens, et al., ; Hearn et al., ; Macdonald, Bothwell, et al., ; Macdonald, Cushman, et al., ) species. Previous studies of N. nebulosa in Bhutan (Penjor et al., ) and of N. diardi in Borneo and Sumatra (Hearn et al, ; Hearn, Cushman, Ross et al., ; Macdonald, Bothwell, et al., ; Macdonald, Cushman, et al., ; Sollmann et al., ) also found positive associations with ridgelines and slope, and negative associations increased with density of human settlements and land use intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Closed‐canopy forests are a primary requirement for this semi‐arboreal species (Cushman et al., ; Sollmann, Linkie, Haidir, & Macdonald, ; Tan et al., ). Conversely, deforestation and subsequent land conversion to large‐scale palm and Acacia plantations have been identified as major threats for both the mainland (Tacconi, ) and Sunda (Cushman et al., ; Hearn et al., ; Hearn, Cushman, Goossens, et al., ; Hearn et al., ; Macdonald, Bothwell, et al., ; Macdonald, Cushman, et al., ) species. Previous studies of N. nebulosa in Bhutan (Penjor et al., ) and of N. diardi in Borneo and Sumatra (Hearn et al, ; Hearn, Cushman, Ross et al., ; Macdonald, Bothwell, et al., ; Macdonald, Cushman, et al., ; Sollmann et al., ) also found positive associations with ridgelines and slope, and negative associations increased with density of human settlements and land use intensity.…”
Section: Methodsmentioning
confidence: 99%
“…Individual species responses to logging regimes vary, but research is increasingly showing that selectively logged Bornean forests can retain considerable levels of pre-disturbance biodiversity (e.g., Meijaard et al 2005;Costantini et al 2016), as well as the capacity to serve as corridors for less disturbance tolerant species moving between intact forest fragments. The establishment of industrial scale plantations of oil palm Elaeis guineensis, however, can lead to dramatic declines in species richness (e.g., Fitzherbert et al 2008) and greatly inhibit connectivity of forest dependent species (e.g., Hearn et al 2018). Thus, for species of conservation concern on Borneo there is an urgent need for connectivity modelling to assess impacts of landscape change to inform the development of effective conservation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In the first study to explore patterns of connectivity for the Sunda clouded leopard, Brodie et al (2015) used hierarchical modelling of camera-trap data to assess and identify potential dispersal and corridor routes within a transboundary network of protected areas in Borneo. Hearn et al (2018) analysed movement data within a path-selection framework to develop the first multi-scale, empirical connectivity predictions for a population of Sunda clouded leopards in eastern Sabah, and showed that movement is facilitated by forest canopy cover and resisted by non-forest vegetation, particularly plantation areas with low canopy closure. In the only large-scale analysis of Sunda clouded leopard connectivity, Macdonald et al (2018) used spatially synoptic modelling, combining resistant kernel and factorial least cost path analysis (Cushman et al 2013a(Cushman et al , 2014, to predict patterns and changes in connectivity across the entire island of Borneo.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations